A simulated annealing approach for uncapacitated continuous location-allocation problem with zone-dependent fixed cost - Abdullah, Tolhah; Zainuddin, Zaitul Marlizawati; Salim, Sutinah (Department of Mathematics, Faculty of Science, 2008)
Location analysis is concerned with locating one or more service facilities while fulfilling some constraints such as the demand of the customers and minimizing the total cost. Despite the cost of transporting goods or services, there is a fixed cost associated with opening a given facility such as the cost of the land, taxes or trunking (or hauling) cost to supply product, services and labour. This cost may vary from one area to another. The aim of this study is to put forward a Simulated Annealing (SA) procedure for solving the uncapacitated continuous location-allocation problem in the presence of a zone-dependent fixed cost. Simulated Annealing is one of the meta-heuristic methods derived from the annealing process of a solid. Several parameters in SA will be tested such as initial starting points, initial temperature and cooling schedules. Data set for 50 customer problem taken from the literature is used. The problems of locating 2 to 15 facilities are solved by using C++. The computational results are presented with encouraging results.